Critical Analysis on the Implementation of the Pilgrimage Portion Prize Savings Plan from the perspective of National Sharia Board Indonesian Ulema Council - Sunanda Octaviani; Rahmad Hakim; Atut Frida Agustin (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
This study aims to find out how the review of the implementation of the contract on savings plans with pilgrimage portion measures from the perspective of DSN-MUI Fatwa No. 86/DSN-MUI/XII/2012 concerning Prizes in Funding for Islamic Financial Institutions and DSN-MUI Fatwa No. 29/DSNMUI/VI/2002 concerning Financing for Pilgrimage Management of Islamic Financial Institutions. This qualitative research uses research with a case study approach. The data used is primary data that is obtained from interviews. Secondary data was obtained in the form of brochures and circulars of saving plans with pilgrimage portion prizes. The results found that the implementations of the pilgrimage portion prize savings plan were in line with the the light of fatwa, yet there were several provisions were inappropriate, first, on the prizes where the bank in implementing the gift has been agreed at the beginning, namely in the form of a portion of the pilgrimage. Seccond, on the method of giving gifts should not be customary (habit or 'urf) but savings plans with prizes for the pilgrimage portion have been implemented since the end of 2018 until now. Meanwhile, the implementation of the contract in the savings plan with prizes of pilgrimage portion were less conformity with the fatwa.